Investigation of Influence Factors of Wind-Induced Buffeting Response of a Six-Tower Cable-Stayed Bridge - Zhi-Qiang Zhang; You-Liang Ding; Fang-Fang Geng (Shock and Vibration)
This paper presents an investigation of the wind-induced buffeting responses of the Jiashao Bridge, the longest multispan cable-stayed bridge in the world. A three-dimensional finite element model for the Jiashao Bridge is established using the commercial software package ANSYS and a 3D fluctuating wind field is simulated for both bridge deck and towers. A time-domain procedure for analyzing buffeting responses of the bridge is implemented in ANSYS with the aeroelastic effect included. The characteristics of buffeting responses of the six-tower cable-stayed bridge are studied in some detail, focusing on the effects including the difference in the longitudinal stiffness between the side towers and central towers, partially longitudinal constraints between the bridge deck and part of bridge towers, self-excited aerodynamic forces, and the rigid hinge installed in the middle of the bridge deck. The analytical results can provide valuable references for wind-resistant design of multispan cable-stayed bridges in the future.